2019
DOI: 10.1016/j.jhazmat.2017.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpyrifos degradation via photoreactive TiO2 nanoparticles: Assessing the impact of a multi-component degradation scenario

Abstract: High concentrations of pesticides enter surface waters following agricultural application, raising environmental and human health concerns. The use of photoreactive nanoparticles has shown promise for contaminant degradation and surface water remediation. However, it remains uncertain how the complexity of natural waters will impact the photodegradation process. Here, we investigate the photoreactivity of titanium dioxide nanoparticles, the capability to degrade the pesticide chlorpyrifos, and the effect of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…It was observed that the concentration of chlorpyrifos oxon was higher than the MRLs established by the European Union and the national standards. In two previously conducted studies, the formation of chlorpyrifos oxon was detected and increased toxicity after photodegradation and ultrasonic irradiation; nonetheless, the oxidation of diazinon was not the predominant reaction (25,26).…”
Section: Discussionmentioning
confidence: 92%
“…It was observed that the concentration of chlorpyrifos oxon was higher than the MRLs established by the European Union and the national standards. In two previously conducted studies, the formation of chlorpyrifos oxon was detected and increased toxicity after photodegradation and ultrasonic irradiation; nonetheless, the oxidation of diazinon was not the predominant reaction (25,26).…”
Section: Discussionmentioning
confidence: 92%
“…The 96‐h EC50s of dimethoate that indicate higher toxicity at test series PEST + nTiO 2 than at test series PEST despite more efficient degradation (Table 4) could, in addition, be induced by the formation of metabolites that are more toxic than the parent substance (Evgenidou et al 2006; Farner Budarz et al 2017). It was shown that during photocatalytic degradation with nTiO 2 , dimethoate is degraded into 9 by‐products (Evgenidou et al 2006), whereas the major by‐product, omethoate (Van Scoy et al 2016), is 90‐fold more toxic than the mother compound (Pesticide Properties Database; Lewis et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Different methods have been reported for OPs remediation, such as bioremediation (Chishti et al, 2013;Ishag et al, 2016), photodegradation (Chen et al, 2007;Farner Budarz et al, 2019;Samy et al, 2020), membrane filtration (Ahmad et al, 2008) and adsorption techniques (Jacob et al, 2020;Lazarević-Pašti et al, 2016;Liu et al, 2018;Momić et al, 2016). Among the mentioned methods, adsorption has been considered one of the most suitable techniques for OP removal from an aqueous medium due to its simplicity, cost effectiveness, environment friendliness, and the possibility of scaling up the process (Liu et al, 2018).…”
Section: Dimethoate (Oo-dimethyl S-[2-(methylamino)-2-oxoethyl]mentioning
confidence: 99%